Apixaban and clopidogrel in a fixed-dose combination: Formulation and in vitro evaluation - Ni'meh Al-Shami; Hani Naseef; Feras Kanaze (Saudi Pharmaceutical Journal, 2024)
Fixed-dose combination (FDC) products represent a novel, safe, and cost-effective formulation. Combined use of anticoagulant and antiplatelet medications is common among comorbid cardiovascular patients. This study aimed to formulate FDC tablets for Apixaban and Clopidogrel, as prophylaxis and treatment of thrombo-embolic events. FDC tablets were developed by combining small tablets of Immediate-Release Clopidogrel 75 mg and Extend-Release Apixaban 5 mg through direct compression and wet granulation. Particularly, Apixaban tablets were developed using design expert software, and various types and concentrations of polymers were entered. For Clopidogrel tablets, various diluents were used to develop the formulation. Then, the dissolution profile for each formula was studied. Finally, the optimized formulations were encapsulated within hard gelatin capsules. Apixaban formulation followed zero-order with super case Ⅱ transport mechanism as the dominant mechanism of drug release. The Apixaban drug release rate was affected by the type and concentration of the polymers in the formulation (P < 0.05). As the HPMC concentration was increased, Apixaban release was retarded. For, Clopidogrel, the formulated tablets with spray-dried lactose filler and sodium stearyl fumarate lubricant were found to be stable with good properties. In conclusion, the optimum formulation yielded Clopidogrel and extended-release Apixaban for 24 h with the desired in vitro drug dissolution.